Comparative analysis of the effects of the use of electronic cigarettes and conventional cigarettes on the cardiovascular and respiratory systems (Research, Society and Development, 2023)
Smoking is one of the major public health issues, causing significant morbidity and mortality, and being associated with various diseases affecting both the cardiovascular and respiratory systems. Consequently, the marketing of supposedly healthier alternatives to smoking has surged in recent years, particularly with the advent of electronic cigarettes since the early 21st century, also known as electronic nicotine delivery systems. However, the extent to which these technological alternatives are truly healthier than any other nicotine-based drug remains highly questionable.Therefore, the present study aims to analyze and compare cardiovascular and respiratory responses following the use of electronic cigarettes and conventional cigarettes, in order to determine the potential for asserting that one device is less harmful to health than the other. This literature review was conducted by surveying clinical trials in the PubMED database.The findings suggest that there are differences in the physiological effects of each device, but at the same time, highlight the need for further clinical trials and studies to analyze and confirm their medium and long-term effects.